Impact of the invasive three-spined stickleback (Gasterosteus aculeatus) on relative abundance and growth of native pelagic whitefish (Coregonus wartmanni) in Upper Lake Constance - Rösch, Roland; Baer, Jan; Brinker, Alexander (Hydrobiologia, 2018)
Since 2013, the pelagic zone of Upper Lake Constance (ULC) has been subject to a massive invasion of the non-native three-spined stickleback ( Gasterosteus aculeatus Linnaeus, 1758). Data from monthly monitoring of pelagic whitefish ( Coregonus wartmanni Bloch, 1784) were used to compare weight-at-age and abundance of pelagic whitefish for years before (1997–2012) and after the invasion (2013–2015). Growth and abundance of pelagic whitefish is shown to be heavily influenced by stickleback presence. Mean autumn weight-at-age of whitefish decreased by 33.3% after the invasion took place and a significant decline in autumn CPUE in otherwise unfished cohorts of the population was also recorded. The results imply direct effects of stickleback presence on pelagic whitefish, including interspecific competition for food leading to reduced growth and survival, and predation of eggs and larvae, hampering recruitment. These observations coincide with a sharp decline in whitefish yield. In conclusion, this study shows that the invasion of stickleback has substantially altered the pelagic fish community of ULC, with severe consequences for commercial fisheries.